From languageless interaction to enlanguaged interaction : a philosophical study of Ildefonso :a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Philosophy at Massey University, Palmerston North, New Zealand - Mackenzie, Anne Jennifer; Mackenzie, Anne Jennifer (Massey University, 1999)
This investigation centres on a man, Ildefonso, learning his first language (American Sign Language) at twenty-seven. The prime source of material is Susan Schaller's account of teaching Ildefonso, A Man Without Words. Certain claims about language and education from the Deaf community, and writings of the Deaf are a second important source of material. The deaf individual, not the theory of language as such, is the focus of the issue of languagelessness in these materials and in this dissertation. Schaller's account throws doubt on some conventional notions of language, and an alternative view of language emerges. Her early lessons are based on conventional ideas: that language is fundamentally a symbol system; that language is a tool for transferring information; that vocabulary and grammar are of prime importance. Lessons based on these ideas fail with Ildefonso. Progress occurs when Schaller stops trying to show Ildefonso ASL signs and begins trying to confer with him. Her description of his progress suggests languaging is fundamentally a particular kind of interaction. I characterise this as reciprocal back and forth interaction, and trace its development in three dialogues between Schaller and Ildefonso. One of the most surprising features of this development is the secondary nature of sign/words and grammar to becoming enlanguaged. Some years later, Schaller asks Ildefonso about his thinking before he acquired ASL. He gives none of the conventional answers we might expect. After two failed attempts to answer he takes Schaller to meet some of his languageless friends so that she can see for herself. Clearly he wants her to see interaction. I have characterised this interaction as performer-audience interaction. Humberto Maturana's theory of language, based on the interaction of living systems, provides a framework which accommodates both performer-audience interaction and reciprocal back and forth interaction. The transition to becoming enlanguaged has more to do with coming to interact in a particular way than with acquiring a vocabulary or learning grammar. Language is fundamentally a particular way of interacting. This view of language helps us understand why bilingual education (incorporating a signed language) is important for profoundly deaf children. We see why sign systems devised and imposed by the hearing do not work, but home sign systems generated by deaf children do.
Keywords: Sign language; Communication; Deafness; Language